Penerapan Model Pembelajaran Kooperatif Tipe Student Facilitator and Explaining untuk Meningkatkan Hasil Belajar Siswa Kelas XI-IPS di MA Darul Huda Wonodadi Blitar - Wahyuni, Dwi (Universitas Insan Budi Utomo, 2024)
This Classroom Action Research (PTK) was designed with the aim of describing the improvement in learning outcomes of class XI-IPS students at MA. Darul Huda Wonodadi Blitar by applying the Student Facilitator and Explaining type cooperative learning model. Data collection techniques in research include interview techniques, observation, documentation and tests. n this research, the researcher identified the following research variables: (1) the teacher's ability to manage the class; (2) the critical thinking skills activity variable of students using the Student Facilitator and Explaining learning method on the main subject of Employment in class XI-IPS MA. Darul Huda Wonodadi Blitar; (3) variable student learning outcomes in economics subjects. The research procedure applied in this research uses a series of Action Research Classrooms consisting of 2 cycles with stages, namely the planning stage, implementation stage, observation stage, and reflection stage. The data analysis technique is carried out by data reduction and data exposure. The data reduction process was carried out by selecting students, simplifying and transforming the data that had been presented in the field note transcript. The results of the research showed that the student learning outcomes in cycle I obtained a classical learning completeness score with an average class reaching 75% and in cycle II the class average of classical learning completeness reached 87.5%, so it can be seen if learning is implemented using using the Student Facilitator and Explaining method can improve the learning outcomes of XI-IPS MA students. Darul Huda Wonodadi Blitar.